2020
DOI: 10.3389/fneur.2020.576121
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sex and Gender on the Multidisciplinary Management of Care for Persons With Parkinson's Disease

Abstract: The impact of sex and gender on disease incidence, progression, and provision of care has gained increasing attention in many areas of medicine. Biological factors-sex-and sociocultural and behavioral factors-gender-greatly impact on health and disease. While sex can modulate disease progression and response to therapy, gender can influence patient-provider communication, non-pharmacological disease management, and need for assistance. Sex and gender issues are especially relevant in chronic progressive diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…Women may also experience significant side effects that were not seen in the study population dominated by men that participated in the original seeding trials. Such differences have also been observed in PD [31].…”
Section: Relevance Of Researchsupporting
confidence: 65%
“…Women may also experience significant side effects that were not seen in the study population dominated by men that participated in the original seeding trials. Such differences have also been observed in PD [31].…”
Section: Relevance Of Researchsupporting
confidence: 65%
“…We also included sex to explore if disease-related changes in sensorimotor oscillatory activity differed between males and females, as there are well-documented sex differences in the manifestation of PD. 1,65 Male sex is a risk factor for developing PD, with an average incidence ratio of approximately 2:1 male-female ratio across all stages of the disease. 66 The disease onset is on average two years earlier in males than females and differs in the initial manifestation of symptoms, with women more likely to develop tremor specific symptoms and men more likely to develop rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders are also common in PD, and inconsistent with the results of clinical studies, the prevalence has been reported to be higher in men than in women ( 26 , 27 ). Based on the sex-related effects of PD on non-motor symptoms, female PD patients should pay more attention to negative emotions, for which they may need guidance from clinical staff and caregivers ( 28 ).…”
Section: Discussionmentioning
confidence: 99%